An empirical study of the impact of macroeconomic variables on the capital structure of South African firms during periods of heightened economic uncertainty - Plaatjies, Marvin (Department of Finance and Tax, 2025)
In this empirical research, the impact of national debt to GDP (and other selected macroeconomic variables) on the capital structure of South African firms is investigated during a period of heightened economic uncertainty. Economic uncertainty, as defined in this study, refers to the degree of unpredictability and lack of confidence that exist in the economic environment. In the context of South Africa, economic uncertainty is attributed to the year- on-year overall deterioration of key macroeconomic variables (my variables of interest), namely the national debt to GDP, GDP growth rate, inflation rate, interest rates, and tax rate. This research is built on previous research conducted by Pierre Erasmus in 2010, which covered the capital structure, and the debt maturity decision, of South African firms during the period between 1989 to 2008. Erasmus mainly considered the following macroeconomic variables: GDP, inflation rate, growth rate, and exchange rate. I have expanded on the study of Erasmus by incorporating other macroeconomic variables, including national debt to GDP, interest rates, and tax rate. I conducted generalised method of moments (GMM) alongside pooled Ordinary Least Squares (OLS) and performed a series of endogeneity checks using alternative regression models. The findings of this study, which are explained by the pecking order theory, indicate that national debt to GDP, inflation rate and tax rate are important factors that influence the capital structure decisions of South African firms. The study concludes that South African firms tend to exhibit a risk averse nature towards gearing and prefer equity finance over debt financing. Pierre Erasmus also concluded that South African firms adjust their capital structure choices in response to the evolving economy and prefer equity finance over debt finance.